FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPEREMESIS GRAVIDARUM PADA IBU HAMIL DI POLIKLINIK RUMAH SAKIT ISLAM BANJARMASIN - Hijrawati, Nani; Sari, Yenny Okvita; Wulandatika, Darmayanti (STIKES Suaka Insan, 2023)
Hyperemesis gravidarum is severe or excessive nausea and vomiting during pregnancy. Continuous vomiting without treatment can disrupt fetal growth and development in the uterus with its clinical manifestations. Hyperemesis gravidarum not only threatens the lives of pregnant women, has a physiological impact on the lives of pregnant women and their fetuses, and can also have psychological, social, and economic effects. This study aims to determine what factors are associated with the incidence of hyperemesis gravidarum in pregnant women using a quantitative approach with the correlation method. The population in this study was 45 people, and the sample was the same as the population; the sampling technique used was total sampling. This data analysis used the Chi-Square test. This study's results indicated a relationship between age, parity, occupation, and education with the incidence of hyperemesis gravidarum in pregnant women at RS Islam Banjarmasin. Chi-square results showed that there was a relationship between the age of pregnant women and hyperemesis gravidarum with a p-value of 0.000 <0.05, there was a relationship between parity and hyperemesis gravidarum with a p-value of 0.000 <0.05, there was an occupational relationship with hyperemesis gravidarum with a p-value of 0.000 <0.05, there was a relationship between education and hyperemesis gravidarum with a p-value of 0.000 <0.05. Keywords: Age, Education, Hyperemesis Gravidarum, Occupation, Parity